2012
DOI: 10.21837/pmjournal.v10.i3.103
|View full text |Cite
|
Sign up to set email alerts
|

The Construction and Demolition Wastes in Klang Valley, Malaysia

Abstract: Numerous activities in construction and demolition (C&D) projects are generally considered as complex and di stant that may affect surrounding environment and public health. Construction, remodell ing, repairing, refurbishing or demotion works of buildings and other infrastructures such as roads generate huge amounts of hazardous and non-hazardous materials. In the present work, an attempt has been made to highlight a number of issues in C&D waste management in the Klang valley of Malaysia and which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In Hong Kong, it is estimated at 23%, which amounts to 20m t (Poon and Chan, 2007). In Malaysia, the CDW accounts for approximately 41% of total solid waste generation (Eusuf et al, 2012). Malaysian CDW is estimated at 161.19 t per day in 2009, increasing to 299.69 t per day in 2015, and is projected to reach 368.31 t per day by 2023 (Fauziah and Agamuthu, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In Hong Kong, it is estimated at 23%, which amounts to 20m t (Poon and Chan, 2007). In Malaysia, the CDW accounts for approximately 41% of total solid waste generation (Eusuf et al, 2012). Malaysian CDW is estimated at 161.19 t per day in 2009, increasing to 299.69 t per day in 2015, and is projected to reach 368.31 t per day by 2023 (Fauziah and Agamuthu, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the nature of design and build in Malaysian projects that are made up of concrete structures. Basically, a concrete waste material was made up of cement, coarse aggregate, fine aggregate, admixtures and right amount of water to achieve the desired bonding for civil structures [7,8]. It is recorded that almost 25 billion tonnes of concrete materials are produced on an annual basis throughout the world to fully fill the demand from construction parties [7].…”
Section: Concretementioning
confidence: 99%
“…This is the major reason for concrete related industries around the world to be known as the massive contributor to the waste materials and the environment impacts [22]. The concrete materials are wasted at the construction site due to the order of inappropriate amounts and the design mix error by the batching plants which fail to be in the range of approved slump once the concrete is poured and tested from the ready mixed truck [8,9]. Concrete materials that are wasted or rejected from the ready mixed truck at the construction site are made up of cement in the highest proportion that possesses several hazardous compounds to increase the strength, durability and maintain the right setting time in cold and hot weather.…”
Section: Concretementioning
confidence: 99%
“…Therefore, the Malaysian government has recommended an assortment of construction waste management. Regrettably, it is yet to accomplish the level of usefulness demanded in dealing with construction waste (Eusuf et al, 2012). Ismam and Ismail (2014) indicated that the Malaysian government is accountable to enhance the implementation of waste management in the construction sector regarding guideline, policy, regulation, and technology.…”
Section: Theoretical Evaluation Of Construction Practices and Waste Gmentioning
confidence: 99%